Constitutional interpretation in Ecuador: A critical review of current theories and practices - Tapia Vélez, Ángel Enrique; Rodríguez Tagle, Cristhian Alí (Revista Universidad de Guayaquil, 2024)
The legal article developed allowed a detailed analysis of the current theories and practices of constitutional interpretation in Ecuador, analyzing the different existing positions and their impact on the application of the Constitution. Through the critical review of the theories and practices of normative interpretation in Ecuador, a descriptive methodology under a qualitative approach, of a basic-documentary nature, and the use of Analytical-Synthetic methods, the exegetics of constitutional norms and the method comparative, highlighted the relevance of constitutional interpretation to maintain the coherence and unity of the legal system. It was established that this task varies from one country to another and is based on the doctrine of originality, that is, maintaining the essence of the writers of the Magna Carta. Likewise, by investigating specifically in the Ecuadorian context, the methods and techniques used in this matter were identified, which are based on national legislative rules. These complement each other and must be used appropriately to achieve a comprehensive and systematic interpretation of constitutional norms. Therefore, constitutional interpretation in Ecuador is considered a fundamental tool of the constitutional legal system, since it provides the Constitutional Court with a wide capacity to select the appropriate methods of interpretation, which may vary over time depending on the doctrine. and related case law. In addition, this tool enables the investigation of the law established in the constitutional laws and explores all the facets that cover its legal and social content, promoting the use of techniques and approaches that guarantee the rights of Ecuadorian citizens.